Socio-demographic and trauma-related predictors of depression within eight weeks of motor vehicle collision in the AURORA study. Issue 10 (29th July 2022) - Joormann, Jutta; McLean, Samuel A.; Beaudoin, Francesca L.; An, Xinming; Stevens, Jennifer S.; Zeng, Donglin; Neylan, Thomas C.; Clifford, Gari; Linnstaedt, Sarah D.; Germine, Laura T.; Rauch, Scott L.; Musey, Paul I.; et al.
Abstract: Background: This is the first report on the association between trauma exposure and depression from the A dvancing U nderstanding of R ec O very afte R traum A (AURORA) multisite longitudinal study of adverse post-traumatic neuropsychiatric sequelae (APNS) among participants seeking emergency department (ED) treatment in the aftermath of a traumatic life experience. Methods: We focus on participants presenting at EDs after a motor vehicle collision (MVC), which characterizes most AURORA participants, and examine associations of participant socio-demographics and MVC characteristics with 8-week depression as mediated through peritraumatic symptoms and 2-week depression. Results: Eight-week depression prevalence was relatively high (27.8%) and associated with several MVC characteristics (being passenger v. driver; injuries to other people). Peritraumatic distress was associated with 2-week but not 8-week depression. Most of these associations held when controlling for peritraumatic symptoms and, to a lesser degree, depressive symptoms at 2-weeks post-trauma. Conclusions: These observations, coupled with substantial variation in the relative strength of the mediating pathways across predictors, raises the possibility of diverse and potentially complex underlying biological and psychological processes that remain to be elucidated in more in-depth analyses of the rich and evolving AURORA database to find new targets for intervention and new tools for risk-based stratification following trauma exposure.